A SIMPLE, INEXPENSIVE, "MODIFIED LASSO" FOR REMOVAL OF SMOOTH, SPHERICAL INTRAOCULAR FOREIGN BODIES. Issue Volume 16:Issues 3(2022) (20th May 2022) - Rice, James C.; Steffen, Jonel; Nyaka, Tamara; van der Westhuizen, Dean
Abstract : Supplemental Digital Content is Available in the Text. Removal of spherical foreign bodies from the posterior segment can be facilitated by constructing a modified lasso with suture material and an intravenous cannula. These items are readily available and inexpensive. Combined use of an intraocular magnet and modified lasso may be useful in the case of a magnetic pellet. Abstract : Purpose: To report and demonstrate removal of an intraocular metallic spherical pellet and to describe the construction of a basket instrument. Methods: A 9-year-old boy sustained a pellet gun injury and underwent pars plana vitrectomy to remove an intraocular spherical metallic pellet. A suture loop basket constructed with 3-O nylon and 16-gauge intravenous cannula was used to grasp and remove the foreign body. Results: The pellet was mobilized from a subretinal position and effectively captured in the basket using the light pipe as a second instrument. The captured pellet was successfully removed without slippage via a scleral tunnel incision. Despite reattachment of the retina under silicone oil, the vision deteriorated to no light perception. Conclusion: A simple, readily available basket can be constructed for the effective removal of spherical foreign bodies which are difficult to grasp.